Biomechanics of the lead straight punch of different level boxers - Liu, Yang; Zhu, Zhiqiang; Chen, Xiuxiu; Deng, Chengyuan; Ma, Xiujie; Zhao, Bin (Frontiers in Physiology, 2022)
We analyze and compare the differences in biomechanical parameters between the lead straight punch and index of force development of the lower extremities of boxers of different levels. To this end, we employed a Vicon infrared 3D motion capture system, two Kistler platforms, a Kistler target and a synchronous instrument. Sixteen boxers were recruited and sorted into the elite group [height 181.14 ± 3.01 cm, body mass 76.00 ± 10.028 kg] and the junior group [179.67 ± 5.84 cm, body mass 75.47 ± 12.19 kg], after which they were compared and analyzed in terms of their lead straight punch. Three punch velocity indexes, six strength indexes, and four exertion of both legs indexes were selected for the analysis. Significant differences in the peak punch velocity and contact velocity were found between the two groups (Cohen’s d = 1.89 , Cohen’s d = 1.34, p < 0.01, p < 0.05). Furthermore, significant differences were noted in the peak force, relative strength, impulse, and rate of force development (RFD) (Cohen’s d = 1.43 , Cohen’s d = 1.19 Cohen’s d = 1.85, Cohen’s d = 1.45 , p < 0.01, p < 0.05). Among the four indexes of the lower extremities from two embedded Kistler force platforms. there are significant differences in lead leg of peak force/body mass (Cohen’s d = 1.92 , p < 0.05), RFD index, RFD /body mass index (Cohen’s d = 1.72, Cohen’s d = 1.64, p < 0.05). There is no significant differences in the four indexes on the rear leg between the two groups (p＞0.05). Based on the disparity in the effect of the lead straight punch and biomechanical parameters of both lower extremities, the boxers must attach importance to sequential acceleration-barking training to improve the terminus velocity of the hand, and thus to improve the contact velocity. Further, it is advised that coaches and practitioners carefully consider to increase the start-up strength training of the lead leg and attempt to improve the peak velocity of the lead straight punch. To accomplish these goals, exercises like unilateral stretch-shortening cycle training and plyometric resistance training are recommended.